Connotation and practice of the integration of academic field based on Bourdieu’s theory——taking the cultivation of cyberspace security talents as an example - Qian ZHOU; Haiping HUANG; Le WANG; Yanchun ZHANG; Fu XIAO (网络与信息安全学报)
The deployment of network security has become a crucial strategy for the development of modern nations, with skilled professionals serving as the core driving force behind cybersecurity efforts.Cultivating cybersecurity talents and fostering team building are essential for China's talent reserves and strategic capital accumulation.With economic globalization, 0-day vulnerabilities have constantly emerged in information systems, attack chains have become increasingly complex, threat targets were difficult to detect, and hidden viruses varied over time.Talents trained by traditional universities for network security were unable to adapt to innovative production and practical activities in the new fields, as it was confined to their training structure system.In order to break through the shackles of the internal administrative structure and traditional curriculum system of universities, and ease the contradiction between the uncertainty of cyberspace security situation and the standardization of talent cultivation, the talent cultivation models based on Bourdieu's theory were studied, the fusion meaning of cultural capital in the academic field was analyzed and three practical standards were put forward in terms of teaching content, cultivation model and teaching opportunity of cyberspace security talents in combination with the actual cases of the “Fang class”.In terms of education content, standards and open knowledge systems were established to meet the differentiated needs of students.The mentorship approach was employed to construct habitus, fostering students’ ability to adapt flexibly to problems by adopting different cognitive thinking modes.Favorable teaching opportunities were utilized by tutors in various roles to promote efficient integration of individuals and fields, helping students establish a valuable and stable mindset.By leveraging Bourdieu's theory to explore the integration path of academic fields, it has leveraged the advantages of independently cultivating high-quality talents, vigorously promoting technological innovation and the healthy ecological development of the industry.